Full squat produces greater neuromuscular and functional adaptations and lower pain than partial squats after prolonged resistance training - Pallares, J. G.; Cava, A. M.; Courel-Ibanez, J.; Gonzalez-Badillo, J. J.; Moran-Navarro, R. (European Journal of Sport Science, 2020)
The choice of the optimal squatting depth for resistance training (RT) has been a matter of debate for decades and is still controversial. In this study, fifty-three resistance-trained men were randomly assigned to one of four training groups: full squat (F-SQ), parallel squat (P-SQ), half squat (H-SQ), and Control (training cessation). Experimental groups completed a 10-week velocity-based RT programme using the same relative load (linear periodization from 60% to 80% 1RM), only differing in the depth of the squat trained. The individual range of motion and spinal curvatures for each squat variation were determined in the familiarization and subsequently replicated in every lift during the training and testing sessions. Neuromuscular adaptations were evaluated by one-repetition maximum strength (1RM) and mean propulsive velocity (MPV) at each squatting depth. Functional performance was assessed by countermovement jump, 20-m sprint and Wingate tests. Physical functional disability included pain and stiffness records. F-SQ was the only group that increased 1RM and MPV in the three squat variations (ES = 0.77-2.36), and achieved the highest functional performance (ES = 0.35-0.85). P-SQ group obtained the second best results (ES = 0.15-0.56). H-SQ produced no increments in neuromuscular and functional performance (ES = -0.11-0.28) and was the only group reporting significant increases in pain, stiffness and physical functional disability (ES = 1.21-0.87). Controls declined on all tests (ES = 0.02-1.32). We recommend using F-SQ or P-SQ exercises to improve strength and functional performance in well-trained athletes. In turn, the use of H-SQ is inadvisable due to the limited performance improvements and the increments in pain and discomfort after continued training.